Effect of the Amount of Mineral Powder on the Ultraviolet Aging Properties of Asphalt - Xiangbing Xie; Shenjia Tong; Yabi Ding; Hongni Liu; Linyuan Liang (Advances in Materials Science and Engineering)
Mortar has an important influence on the viscosity and durability of a mixture. The effects of the amount of mineral powder in asphalt mortar on the ultraviolet (UV) aging properties of asphalt were investigated by a Fourier transform infrared spectrum (FTIR), gel permeation chromatography (GPC), and dynamic shear rheometer (DSR). The FTIR results show that the UV-resistant aging ability of asphalt mortar was superior to asphalt and that the carbonyl indices of the SBS- (styrene-butadiene-styrene-) asphalt mortar and matrix asphalt mortar were more significant. The GPC results show that the molecular weight distribution coefficient (Mw/Mn) of the SBS-asphalt-filler mastic is 1.0 and that of the matrix asphalt-filler mastic is 1.2, which is the largest. The macro-property is the most stable. The DSR results show that the matrix asphalt-filler mastic ranging from 1.0 to 1.2 and the SBS-modified asphalt-filler mastic ranging from 0.8 to 1.0 show the best UV aging resistance. Therefore, the effects of the amount of mineral powder cannot be ignored, suggesting that the best mass ratio of the matrix asphalt mortar is 1.2 and that of the SBS-modified asphalt mortar is 1.0 during the UV aging process.